2017
DOI: 10.1093/icvts/ivx081
|View full text |Cite
|
Sign up to set email alerts
|

Vasoplegia after heart transplantation: outcomes at 1 year†

Abstract: Although vasoplegia syndrome was associated with an increase in perioperative morbidity, including greater mechanical ventilation time and hospital length of stay, no significant differences in survival or allograft rejection at 1 year was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 26 publications
0
41
1
Order By: Relevance
“…In another study, ≈48% and 34% of patients undergoing CPB developed vasoplegia immediately and 24 hours following surgery, respectively, based on mean arterial pressure <50 mm Hg and the need for noradrenaline perfusion >0.08 μg/kg per minute . Another study reported a rate of 31% among heart transplant patients, with vasoplegia defined as “global systemic hypotension within 48 hours of heart transplantation with concurrent requirement of vasopressor administration (eg, vasopressin, epinephrine, or norepinephrine infusion of >5 μg/min) for >24 hours to maintain MAP [mean arterial pressure] >70 mm Hg.” Similarly, in the Esmailian heart transplant study, 34% developed vasoplegia (with the majority categorized as mild) . We adopted Chan and colleagues’ definition of vasoplegia and observed a rate of 49%, which was the highest of the studies reviewed and may be explained by the greater severity of illness in LVAD patients compared with heart transplantation patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In another study, ≈48% and 34% of patients undergoing CPB developed vasoplegia immediately and 24 hours following surgery, respectively, based on mean arterial pressure <50 mm Hg and the need for noradrenaline perfusion >0.08 μg/kg per minute . Another study reported a rate of 31% among heart transplant patients, with vasoplegia defined as “global systemic hypotension within 48 hours of heart transplantation with concurrent requirement of vasopressor administration (eg, vasopressin, epinephrine, or norepinephrine infusion of >5 μg/min) for >24 hours to maintain MAP [mean arterial pressure] >70 mm Hg.” Similarly, in the Esmailian heart transplant study, 34% developed vasoplegia (with the majority categorized as mild) . We adopted Chan and colleagues’ definition of vasoplegia and observed a rate of 49%, which was the highest of the studies reviewed and may be explained by the greater severity of illness in LVAD patients compared with heart transplantation patients.…”
Section: Discussionmentioning
confidence: 92%
“…We compiled data on consecutive patients undergoing LVAD implantation surgery from June 2008 to May 2016 at the Baylor University Medical Center, after receiving approval from Baylor Scott and White Research Institute's institutional review board (with a waived requirement of informed consent). We followed the framework of Chan and colleagues by defining vasoplegia as the occurrence of normal cardiac function and index but with the need for intravenous vasopressors within 48 hours following surgery for >24 hours to maintain a mean arterial pressure >70 mm Hg . As in Esmailian and colleagues’ work, we further categorized vasoplegia as none ; mild , requiring 1 vasopressor (vasopressin, norepinephrine, or high‐dose epinephrine [>5 μg/min]); or moderate to severe , requiring ≥2 vasopressors .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recipients, especially patients who have been on inotropic support and mechanical devices, have activation of their systemic inflammatory response, which causes intense vasodilation and therefore lowering of the systemic vascular resistance. The net result is a hypotensive state despite adequate filling and a high cardiac output that is refractory to vasopressor support [64]. The exact pathogenesis of this is poorly understood to date, some mechanisms have been postulated.…”
Section: Primary Graft Dysfunctionmentioning
confidence: 99%
“…This syndrome is characterized by hypotension and the continuous need of vasopressors, despite a normal or high cardiac index. The incidence of vasoplegia ranges from 11 to 31% in patients undergoing heart failure surgery [5][6][7][8][9]. The prognosis of vasoplegia is poor.…”
Section: Introductionmentioning
confidence: 99%